Cultural Values' Integration in Character Development in Elementary Schools: The Sukuraga as Learning Media - Nurasiah, Iis; Sumantri, Mohamad Syarif; Nurhasanah, Nina; Casmana, Asep Rudi (Frontiers in Education, 2022)
The purpose of this study was to analyze the character development of students through the use of the Puppet Sukuraga application. It can be seen that, during the Covid-19 pandemic, fulfilling the affective dimension tended to be ignored by teachers, who instead emphasized the cognitive dimension. In the affective dimension, Puppet Sukuraga is used as a character education tool in the form of applications that can develop students' character. This puppet can also be used on mobile phones by students who understand the Sukuraga wayang in depth. This study uses a mix-method conducted in one of the elementary schools in Indonesia that already uses the Puppet Sukuraga application. The number of participants in this study were two 10 teachers and 60 students in the second grade, so that overall, there were 60 participants. Data is provided in the form of a detailed description of the subject's activities from the subject's perspective through interviews and group discussion forums. Online survey for the descriptive statistical analysis was used and in-depth interviews were also used for teachers and students. It was conducted 45 min before and after learning in class. The results of the study show that the use of the Puppet Sukuraga application can develop students' character, particularly characteristics of tolerance and responsibility. Students' tolerance is more developed, and it can be seen from the attitude of respect for differences in religion, ethnicity, habits, and differences of opinions. The characteristic of responsibility is also more developed, such as being responsible for their duties in doing homework, being responsible for carrying out the teacher's orders, and being responsible for carrying out useful activities. This research has implications for elementary school teachers in Indonesia during the limited online and face-to-face learning period. It can be concluded that the cultural values on the Sukuraga Puppet Application can help teachers in schools teach students about character enhancement.